1993
DOI: 10.1073/pnas.90.24.11845
|View full text |Cite
|
Sign up to set email alerts
|

The presequence of Euglena LHCPII, a cytoplasmically synthesized chloroplast protein, contains a functional endoplasmic reticulum-targeting domain.

Abstract: The precursor to the Euglena light-harvesting chlorophyll a/b-binding protein of photosystem II (pLHCPII) is unique; it is a polyprotein, synthesized on membrane-bound ribosomes and transported to the Golgi apparatus prior to chloroplast localization. A cDNA corresponding to the 5' end of LHCPII mRNA has been isolated and sequenced. The deduced amino acid sequence of this cDNA indicates that Euglena pLHCPII contains a 141-amino acid N-terminal extension. The N-terminal extension contains three hydrophobic doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 31 publications
4
55
0
Order By: Relevance
“…The Euglena pLHCPII is inserted cotranslationally and anchored within canine microsomal membranes, and the N-terminal presequence is removed (Kishore et al, 1993). The in vivo pulse-chase experiments demonstrated that the pSSU was targeted to the ER and Golgi apparatus before chloroplast import.…”
Section: An Uncleaved Signal Peptide Anchors the Pssu In Microsomal Mmentioning
confidence: 99%
See 3 more Smart Citations
“…The Euglena pLHCPII is inserted cotranslationally and anchored within canine microsomal membranes, and the N-terminal presequence is removed (Kishore et al, 1993). The in vivo pulse-chase experiments demonstrated that the pSSU was targeted to the ER and Golgi apparatus before chloroplast import.…”
Section: An Uncleaved Signal Peptide Anchors the Pssu In Microsomal Mmentioning
confidence: 99%
“…In vitro, the pLHCPII is cotranslationally inserted into canine microsomes, processed by signal peptidase, and anchored within the microsomal membrane (Kishore et al, 1993). The pLHCPII and pSSU presequences are structurally similar, containing an N-terminal signal peptide domain and an additional hydrophobic domain that could function as a stop transfer membrane anchor sequence.…”
Section: Pssu Is Transported From the Golgi Apparatus To The Chloroplmentioning
confidence: 99%
See 2 more Smart Citations
“…41,42) In these organisms, plastids are also surrounded by additional membrane layers that are reminiscent of host plasma membranes. Therefore, proteins destined for these plastids are first delivered via a secretory pathway and then translocate across the typical plastid envelope, probably through the TOC-TIC pathway.…”
Section: Targeting Of Glycoprotein To Plastids Via the Secretory Pathwaymentioning
confidence: 99%